Peran Pelatihan Program Kartu Prakerja Dalam Pemberdayaan Masyarakat (Studi Kasus Masyarakat Kota Langsa Penerima Bantuan Program Kartu Prakerja) - Mastura Mastura; Siti Dwi Yana; Fahriansyah Fahriansyah (TANSIQ: Jurnal Manajemen dan Bisnis Syariah, 2022)
This study aims to determine the implementation of the Pre-Employment Card Program and the role of the Pre-Employment Card Program training in community empowerment in Langsa City. The research method used is field research using a qualitative research approach using descriptive methods. Based on the results of research in the implementation of the Pre-Employment Card Program, the steps that must be fulfilled are creating a Pre-Employment Card account, filling in personal data, taking tests, determining acceptance of Pre-Employment Cards, and buying and participating in the Pre-Employment Card Program training. And the role of the Pre-Employment Card Program training in Langsa City, when viewed from the main purpose of the Pre-Employment Card Program, which is competency development, not all respondents develop their competencies, only 6 respondents develop them, and other respondents do not develop them. Second, increasing productivity, that only two respondents developed their productivity by selling clothes online and applying for jobs using the Pre-Employment Card Program training certificate and none of the other respondents developed their productivity. And the third is developing entrepreneurship that there are no respondents who create something new and different, the respondents only sell clothes, sell pulses, and fried foods, none of the respondents create new things so that the role of the Pre-Employment Card Program training in community empowerment through community development is not any role.